International arbitration and India : practice, politics, and new comparative perspectives / Jaya Vasudevan Suseela. - Suseela, Jaya Vasudevan (Cambridge University Press, 2026)
This text offers a sound exposition of the theoretical foundations of international arbitration law using a comparative and cross-cultural approach. Exploring the normative approaches and legitimacy crisis in a transnational context, it aims to establish links between the respective legal regimes handling disputes. Identifying pragmatic solutions in the contemporary world of conflicting interests, this book investigates the latest trends in international arbitration law. This book will help readers understand and demonstrate how best to manage the unification efforts to achieve synergies and enhance the legitimacy of a pluralistic world of international arbitration law. The combination of conceptual analysis and archival investigation of landmark case laws provide the reader with a fresh innovative understanding of the depth of international arbitration law.